2020
DOI: 10.1785/0220200005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Major Fault Systems in the Kachchh Intraplate Region, Gujarat, India, by Focal Mechanism and Source Parameters

Abstract: The focal mechanism and source parameters of 41 local earthquakes (Mw 4.0–5.1) that occurred in the Kachchh rift basin, which is seismically one of India’s most active intraplate regions, are determined to characterize various active fault systems in that region. The tectonics in the rift basin are heterogeneous and complex. In the present study, it was found that one-third of the earthquakes exhibit reverse mechanism and three-fourth are either strike slip or have some components of strike slip. Thus, we conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The extension‐related structure of the Kachchh rift basin might have reactivated as a strike‐slip fault during the inversion process as a result of regional compressive stresses developed due to collision between the Indian and Eurasian plates since Neogene, which is consistent with geological and seismological data (Antolik & Dreger, 2003; Biswas & Khattri, 2002; Patriat & Achache, 1984). The focal mechanisms of the majority of aftershocks indicate strike‐slip/reverse faulting in the region (Kamra et al., 2020; Mandal & Horton, 2007). Similar is the case with other strike‐slip faults identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extension‐related structure of the Kachchh rift basin might have reactivated as a strike‐slip fault during the inversion process as a result of regional compressive stresses developed due to collision between the Indian and Eurasian plates since Neogene, which is consistent with geological and seismological data (Antolik & Dreger, 2003; Biswas & Khattri, 2002; Patriat & Achache, 1984). The focal mechanisms of the majority of aftershocks indicate strike‐slip/reverse faulting in the region (Kamra et al., 2020; Mandal & Horton, 2007). Similar is the case with other strike‐slip faults identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that one‐third of the earthquakes exhibit reverse mechanisms and three‐fourths are either strike‐slip or have some components of strike‐slip. Approximately 90% of the earthquakes in the Kachchh region are found to be reverse, strike‐slip, or a combination of both (Kamra et al., 2020). It appears that transpressional tectonics might be dominant in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong motion data from the network operated by ISR have been used in several engineering seismology applications, such as, estimation of source parameters, site characterization, development of ground motion prediction equation and ground motion modeling. The data recorded from the past decade have been used to characterize various sources in the Kachchh rift and other parts of Gujarat (Kamra et al, 2020). It is found from the study that stress drop of earthquakes (M 4.0-5.1) in the Kachchh rift are in the range 2.3-10.4 MPa with an average of 5.3 MPa.…”
Section: Intraplate Regionsmentioning
confidence: 99%